2014
DOI: 10.1016/j.icarus.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentology and climatic environment of alluvial fans in the martian Saheki crater and a comparison with terrestrial fans in the Atacama Desert

Abstract: a b s t r a c tThe deflated surfaces of the alluvial fans in Saheki crater reveal the most detailed record of fan stratigraphy and evolution found, to date, on Mars. During deposition of at least the uppermost 100 m of fan deposits, discharges from the source basin consisted of channelized flows transporting sediment (which we infer to be primarily sand-and gravel-sized) as bedload coupled with extensive overbank mud-rich flows depositing planar beds of sand-sized or finer sediment. Flow events are inferred to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
111
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 112 publications
7
111
0
Order By: Relevance
“…Those paleolakes include candidate playa deposits at the toes of fans [e.g., Morgan et al, 2014], a >100 m deep paleolake in Crater "P" [Kraal et al, 2008] suggested by a common fan frontal-scarp elevation of -2700 m (in our CTX DTMs), and the Eberswalde paleolake (which shares a drainage divide with fans at Holden [Irwin et al, 2004]). Those paleolakes include candidate playa deposits at the toes of fans [e.g., Morgan et al, 2014], a >100 m deep paleolake in Crater "P" [Kraal et al, 2008] suggested by a common fan frontal-scarp elevation of -2700 m (in our CTX DTMs), and the Eberswalde paleolake (which shares a drainage divide with fans at Holden [Irwin et al, 2004]).…”
Section: Implications For Habitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Those paleolakes include candidate playa deposits at the toes of fans [e.g., Morgan et al, 2014], a >100 m deep paleolake in Crater "P" [Kraal et al, 2008] suggested by a common fan frontal-scarp elevation of -2700 m (in our CTX DTMs), and the Eberswalde paleolake (which shares a drainage divide with fans at Holden [Irwin et al, 2004]). Those paleolakes include candidate playa deposits at the toes of fans [e.g., Morgan et al, 2014], a >100 m deep paleolake in Crater "P" [Kraal et al, 2008] suggested by a common fan frontal-scarp elevation of -2700 m (in our CTX DTMs), and the Eberswalde paleolake (which shares a drainage divide with fans at Holden [Irwin et al, 2004]).…”
Section: Implications For Habitabilitymentioning
confidence: 99%
“…These sedimentologic methods require assumptions about flow intermittency or sediment:water ratio, which (for almost all Mars alluvial fans) are poorly constrained [Dietrich et al, 2017]. Therefore, the lower limits obtained from sedimentological methods are short-for example,~3600 years [Morgan et al, 2014]. Moreover, brief (1-100 years) aggradation intervals have been proposed for deltas on Mars that are similar to the alluvial fans in age and volume [Kleinhans et al, 2010;Mangold et al, 2012a;Hauber et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…The composition of overbank deposits is, thus, uncertain. Exposures of clay-rich fine fluvial overbank sediment can be readily eroded by saltating sand (Morgan et al, 2014), even though they are strongly cohesive when dry. Although no clays have been detected by CRISM multispectral observations covering the AD meandering channels, results from the Mars Science Laboratory (MSL) rover show that a high percentage of clays in sediment may not be detected by the CRISM instrument (Bristow et al, 2013).…”
Section: Aeolis Dorsa (Ad) Meanders Marsmentioning
confidence: 99%
“…An important contextual relationship is the concentration of large alluvial fans within less-degraded impact craters on Mars Kraal et al, 2008;Williams and Malin, 2008;Mangold et al, 2012b;Morgan et al, 2014). Local, geologically brief effects of impacts have been implicated for groundwater release, meltwater production, or lake-effect precipitation, which could incise valleys into the crater rim or ejecta (e.g., Newsom et al, 1996;Abramov and Kring, 2005;Morgan and Head, 2009;Barnhart et al, 2010;Harrison et al, 2010;Newsom, 2010;Kite et al, 2011;Mangold et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%